The Pengaruh Google Sites “Ketoprak” terhadap Tingkat Pemahaman dan Capaian Kepatuhan Fasilitas Kesehatan Mitra BPJS Kesehatan KC Purwokerto: Pengaruh Googlesites “Ketoprak” sebagai Dashboard Performance Kepatuhan Terhadap Kontrak terhadap Pemahaman dan Capaian Kepatuhan Terhadap Kontrak Fasilitas Kesehatan Rujukan Tingkat Lanjutan (FKRTL) di Wilayah Kerja BPJS Kesehatan KC Purwokerto - Mitsalina Maulida Hafizh; Unting Patri Wicaksono Pribadi (BPJS Kesehatan, 2023)
This study aims to determine the effect of the compliance performance dashboard through Google Sites which is easily accessed by Health Facilities on the level of understanding and achievement of by Health Facilities compliance with contracts. The method used a quasi-experimental using one research sample and the data analysis used qualitative methods. The results showed that there was an increasing on the understanding of representatives of Management and PIC by Health Facilities regarding Health Facility compliance with contracts and there was an increasing on the Health Facility compliance score with contracts from August 2022 to September 2022. The percentage increase in compliance scores can reach 20%. The results of this study can be used by internal team of BPJS Kesehatan in order to create an application for monitoring the achievement of Health Facility compliance with contracts and for increasing the level of stakeholder engagement